2020
DOI: 10.33365/llj.v1i1.160
|View full text |Cite
|
Sign up to set email alerts
|

Interactional Metadiscourse used in Bloomberg International Debate

Abstract: In delivering an argument, several things must be known, such as the theme, the purpose, and the content of the argument in a debate. Since debate demands critical thinking, debaters need to consider their words’ choice in delivering their argument. In that case, this research aims to analyze the uses of interactional metadiscourse markers that are applied in the Bloomberg International Debate. In doing the analysis, the writers used the descriptive method and proposed Hyland’s theory (2005). As the result of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…In qualitative research the data collected is not in the form of numbers. The data will be analyzed through dialogue, pictures, and scenes (Istiani and Puspita, 2020). The method that the author uses is descriptive qualitative.…”
Section: Methodsmentioning
confidence: 99%
“…In qualitative research the data collected is not in the form of numbers. The data will be analyzed through dialogue, pictures, and scenes (Istiani and Puspita, 2020). The method that the author uses is descriptive qualitative.…”
Section: Methodsmentioning
confidence: 99%
“…Descriptive qualitative research is in written context which is taken from the data source (Amelia & Dintasi, 2017;Amelia & Mertania, 2020). The qualitative research can be identified by the work, the history, the society, and the culture (Istiani & Puspita, 2020). Moreover, this method of research is flexible and it allows to see the data from different perspective (Kuswoyo & Siregar, 2019)…”
Section: Methodsmentioning
confidence: 99%
“…This research used qualitative method as a way to gather the data (Kardiansyah, 2016). Data also can be seen from pictures, dialogue, or scenes (Istiani and Puspita, 2020). This method also tests hypotheses (Farras and Nurmaily, 2020).…”
Section: Methodsmentioning
confidence: 99%